Red blood cell distribution width to albumin ratio and urinary incontinence subtypes in NHANES 2007–2018 - Tingxuan Lv; Yonghui Liu; Jinhui Yang; Mingyue Wang; Cheng Bo (Scientific Reports)
Abstract This study aims to investigate the relationships among a novel inflammatory biomarker, the red blood cell distribution width-to-albumin ratio (RAR), and three different types of urinary incontinence (UI) while evaluating the potential clinical significance of the biomarker. The National Health and Nutrition Examination Survey (NHANES)—which spanned 2007–2018—was used in this investigation. The relationship between the RAR and the prevalence of UI was assessed by logistic regression modeling, restricted cubic spline curve (RCS) analysis, and subgroup analysis. Fully adjusted models revealed a significant positive correlation between the RAR and all three types of UI (SUI: OR 1.23, 95% CI 1.12–1.35; UUI: OR 1.43, 95% CI 1.31–1.56; MUI: OR 1.44, 95% CI 1.27–1.62; all p < 0.05). Dividing the RAR into quartiles illustrated that an increased RAR was positively correlated with UI compared with a decreased RAR (SUI: OR 1.40, 95% CI 1.22–1.60; UUI: OR 1.85, 95% CI 1.60–2.14; MUI: OR 1.81, 95% CI 1.47–2.21; all p < 0.05). A nonlinear, inverted “U”-shaped relationship between the RAR and UI was demonstrated using restricted cubic spline analysis, suggesting that the RAR impacted UI only until reaching a threshold. Additionally, subgroup analysis revealed a stronger link between the RAR and SUI in women than in men (p < 0.05). An increased RAR was correlated with a heightened risk of UI, and RAR was more strongly associated with stress urinary incontinence (SUI) in women than in men. Systematic epidemiologic evidence suggests that the novel inflammatory marker RAR is associated with UI, but more research is needed to determine causality.